The L2 motivational self system from a Chinese perspective: A mixed methods study. Issue 1 (13th September 2015) - Magid, Michael
Abstract : This mixed methods study compares the Second Language (L2) Motivational Self System of 1, 154 middle school and university students from mainland China with a multi-group structural equation modelling (SEM) analysis and ten case studies of university students from mainland China. The main findings are that the issues of family, face, responsibility and pressure that are discussed in the interview data clarify the motivational role of the Chinese family and explain the main relationships of the L2 Motivational Self System identified by the SEM analysis as well as the relationship between the two types of instrumentality and the Ideal L2 Self. Differences in the motivational orientation of the two sub-groups demonstrate the ability of the system to represent different age groups. A comparison of the findings with recent motivational studies in Hungary reveals similarities in terms of the impact of the Ideal L2 Self, Ought-to L2 Self and attitudes towards learning English on the amount of effort that the participants invest in learning English.